2021
DOI: 10.1152/japplphysiol.00380.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific maturation of muscle metabolites carnosine, creatine, and carnitine over puberty: a longitudinal follow-up study

Abstract: Due to the invasiveness of a muscle biopsy, there is fragmentary information on the existence and possible origin of a sexual dimorphism in the skeletal muscle concentrations of the energy delivery-related metabolites carnosine, creatine and carnitine. As these metabolites can be non-invasively monitored by proton magnetic resonance spectroscopy, this technique offers the possibility to investigate if sexual dimorphisms are present in an adult reference population and if these dimorphisms originated during pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Importantly, this was done in a relatively large number of samples obtained from a diverse group of donors. Although a large interindividual variability in anserine content was observed, this was not significantly associated with sex, age, or body mass, despite previous studies indicating that sex and age can affect muscle carnosine content (Everaert et al, 2011 ; Lievens et al, 2021 ; Mannion et al, 1992 ). It is currently unclear whether these factors do not play a similar role in the cardiac muscle or whether our study is not adequately designed to detect such effects.…”
Section: Discussionmentioning
confidence: 54%
“…Importantly, this was done in a relatively large number of samples obtained from a diverse group of donors. Although a large interindividual variability in anserine content was observed, this was not significantly associated with sex, age, or body mass, despite previous studies indicating that sex and age can affect muscle carnosine content (Everaert et al, 2011 ; Lievens et al, 2021 ; Mannion et al, 1992 ). It is currently unclear whether these factors do not play a similar role in the cardiac muscle or whether our study is not adequately designed to detect such effects.…”
Section: Discussionmentioning
confidence: 54%
“…Carnosine-specific signals may also be masked by competing signals from other imidazole-containing molecules. Moreover, Lievens et al have recently reported an approximate 20% higher concentration of carnosine in muscles among males, as compared to females when measured via 1H-MRS in either gastrocnemius or soleus muscles [ 44 ]. While the current study also found a similar trend, studies with an appropriate power and sample size are required to further study this phenomenon.…”
Section: Discussionmentioning
confidence: 99%